Online Advertisement, Online Marketplace, and Price as Intervening Variables in Influencing Product Purchase Decisions - Rini Martiwi; Eulin Karlina; Instianti Elyana; Fera Nelfianti; Nurzalinar Joesah (Budapest International Research and Critics University, 2022)
Technological developments that occur in this era change consumer behavior in making purchasing decisions. Research on consumer purchasing decisions for a product has been done a lot. In this study, the authors aim to re-examine the factors that influence according to the current developments on consumer purchasing decisions on local Culinary UMKM products. In this study, The.factors.that become variables.are Online Advertisement, Online Marketplace, and Prices which are hypothesized to have an effect on Purchase Decisions for Local Culinary UMKM Products. The analytical methodused in this study is path analysis with the help of the SPSS for Windows version 26 statistical program. Respondents were collected from active social media users who had shopped for local UMKM products, both offline and online. Test the hypothesis that is guided by the value of sig.<0.05 then Ha is accepted and if the value is sig.>0.05 then Ha is rejected. This study also shows how significant the influence of Online Advertisement and Online Marketplace on Purchase Decisions directly or indirectly, which is through price as an intervening variable. The results obtained from this study are Online Advertisement, Online Marketplace, and Prices are proven to have a direct influence on Purchase Decisions. In addition, through the intervening variable, the value of the influence of Online Advertisement through Price does not have a significant effect on Purchase Decisions. While the Online Marketplace through Price has a significant influence on Purchase Decisions.